NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI MERTI DESO DI DESA SUKU MENANTI REJANG LEBONG, BENGKULU - Dedik Prianto; Lukman Asha; Guntur Putra Jaya (Paedagogia: Jurnal Pendidikan, 2020)
This study aimed at finding out Islamic education values embedded in the tradition of Merti Deso in Suku Menanti Village, Sindang Jati District, Rejang Lebong Regency, Bengkulu. This study used a descriptive qualitative approach. The data collection techniques used in this study encompassed observation and interviews conducted periodically. After the data were collected, the data were further analyzed by means of Miles, Haberman, and Saldana’s version of stages, namely data selection, data presentation, and drawing conclusion. This study concluded that the Islamic education values embedded in the tradition of Merti Deso were religious and spiritual values, muamalah/social values, and economic values.